Risk factors associated with unintentional house fire incidents, injuries and deaths in high-income countries: a systematic review. Issue 2 (24th January 2017) - Turner, Samantha L; Johnson, Rhodri D; Weightman, Alison L; Rodgers, Sarah E; Arthur, Geri; Bailey, Rowena; Lyons, Ronan A
Abstract : Objective: To identify the distinguishing risk factors associated with unintentional house fire incidents, injuries and deaths. Study design: Systematic review. Methods: A range of bibliographical databases and grey literature were searched from their earliest records to January 2016. To ensure the magnitude of risk could be quantified, only those study types which contained a control group, and undertook appropriate statistical analyses were included. A best evidence synthesis was conducted instead of a meta-analysis due to study heterogeneity. Results: Eleven studies investigating a variety of risk factors and outcomes were identified. Studies ranged from medium to low quality with no high quality studies identified. Characteristics commonly associated with increased risk of house fire incidents, injuries and fatalities included: higher numbers of residents, male, children under the age of 5 years, non-working households, smoking, low income, non-privately owned properties, apartments and buildings in poor condition. Several risk factors were only associated with one outcome (eg, living alone was only associated with increased risk of injurious fires), and households with older residents were at increased risk of injurious fires, but significantly less likely to experience a house fire in the first place. Conclusions: This best evidence synthesis indicates that several resident and property characteristics are associated with risk of experiencing house fire incidents, injuries or death. These findings should be considered by the Fire and Rescue Services and others with a role in fire prevention. Future research should adopt robust, standardised study designs to permit meta-analyses and enable stronger conclusions to be drawn.